FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON-KEUANGAN DI INDONESIA - Mungniyati; Ribka Lia Bevalia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to test and obtain empirical evidence of company size (SIZE), company age (AGE), capital structure (DER), financial performance (ROE), company profit (NPM), managerial ownership (MO), institutional ownership (IO), and liquidity (CR) on firm value. Firm value is measured using the Price to Book Value ratio, also known as PBV. The population or research object used in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. The sampling method used in this study is a purposive sampling method. There are 131 non-financial companies that have met the criteria, so the total sample is 393 data used. The research hypothesis was analyzed using the multiple regression model and the data was processed using SPSS version 25 program. The findings of this research indicate that company size, company age, financial performance, and company profit have an effect on firm value. Meanwhile, capital structure, managerial ownership, institutional ownership, and liquidity have no effect on firm value.